Pengaruh dana perimbangan terhadap ketimpangan pembangunan di Provinsi Jambi - Wanti Oktaviani; Zulgani Zulgani; Rosmeli Rosmeli (Konsentrasi Pembangunan Regional dan Publik, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2017)
This study aims to analyze: 1) inequality of development in Jambi Province; 3) the effect of general allocation funds (DAU), special allocation funds (DAK), and profit sharing funds (DBH) on inequality in development in Jambi Province. The data used are secondary data sourced from the Central Bureau of Statistics of Jambi Province. The data analysis tool uses Williams Index, and path analysis. The results of the study found that 1) The average Williamson Index value in Jambi Province during the period 2001-2016 is 0.392743, which means that there is a high inequality. 2) Simultaneously DAU, DAK, and DBH have a significant effect on inequality. together DAU, DAK, and DBH are able to explain inequality by 80.00%, while the remaining 20.00% is explained by other variables not found in this study. Partially the variables that significantly influence inequality are DBH while DAU and DAK have no significant effect.